2008
DOI: 10.1590/s1678-58782008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Development of asbestos-free friction lining material from palm kernel shell

Abstract: Friction materials are applicable for braking and transmission in various machines and equipment. Their composition keeps changing to keep pace with technological development and environmental/legal requirements. For more than 80 years asbestos has been used as a friction material because of its good physical and chemical properties. However, due to the health hazard associated with its handling, it has lost favour and several alternative materials are being increasingly used. Thus, in this work, a non - asbes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 5 publications
1
40
0
Order By: Relevance
“…These include: the empty fruit bunch (EFB), palm fruit fiber (PFF), palm oil mill effluent (POME) and palm kernel shell (PKS). Whereas oil palm is chiefly cultivated for palm oil (PO) and palm kernel oil (PKO), the PKS (as residue) has been regarded as 'waste' from palm oil processing by Obeng et al (1997), Lartey et al (1999) and Ibhadode and Dagwa, (2008). It has been shown that approximately 15 to 18 tonnes of fresh fruit bunches are produced per hectare per year and PKS comprises about 64% of the bunch mass (Obisesan, 2004;Adewumi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These include: the empty fruit bunch (EFB), palm fruit fiber (PFF), palm oil mill effluent (POME) and palm kernel shell (PKS). Whereas oil palm is chiefly cultivated for palm oil (PO) and palm kernel oil (PKO), the PKS (as residue) has been regarded as 'waste' from palm oil processing by Obeng et al (1997), Lartey et al (1999) and Ibhadode and Dagwa, (2008). It has been shown that approximately 15 to 18 tonnes of fresh fruit bunches are produced per hectare per year and PKS comprises about 64% of the bunch mass (Obisesan, 2004;Adewumi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Taguchi optimization technique was utilised to achieve optimal friction material formulation and optimum manufacturing parameters. A disc brake is investigated with palm karnel shell material [14]. The development of asbestos-free automotive brake pad using periwinkle shell particles as frictional filler is made in some literature.…”
Section: Asbestos Free Brake Lining Materialsmentioning
confidence: 99%
“…A. Ibhadode et al and K. Deepika et al respectively [1,3]. Taguchi optimization technique was used to achieve optimal frict ion material formu lation and manufacturing parameters.…”
Section: Another Materials-mentioning
confidence: 99%
“…The mechanical and physical properties compare well with co mmercial asbestos -based frict ion lining material. Its performance under static and dynamic conditions compare well with the asbestos -based lin ing material [1,3].…”
Section: Another Materials-mentioning
confidence: 99%